Studies on Insect Pest Association in Shisham Based Agrisilviculture System with Special Reference to Pruning Intensity - Sharma, Vishwajeet; Singh, Ved Pal; Behera, Falguni (Indian Forester, 2016)
Dalbergia sissoo Roxb. ex DC. ver. Shisham belongs to family Fabaceae is one of the most important commercially valuable timber species. It is best known for its highly valued timber that widely in use as for timber construction, boats, cart wheels, veneer plywood, bent wood, high quality furniture, cabinets, flooring and turnery works. The present paper deals with the effect of insect pests on different pruning regimes 0%, 25%, 50%, and 75% of Dalbergia sissoo and conducted at Dusty Acres Research Farm, Department of Forestry, Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur during Kharif season of 2012.